2014
DOI: 10.1007/s10570-014-0493-y
|View full text |Cite
|
Sign up to set email alerts
|

Porous electrospun nanocomposite mats based on chitosan–cellulose nanocrystals for wound dressing: effect of surface characteristics of nanocrystals

Abstract: Randomly oriented fiber mats of chitosanpolyethylene oxide matrix reinforced with cellulose nanocrystals (CNCs) were prepared by electrospinning technique. The cellulose nanocrystals used were isolated using hydrochloric acid (CNC HCl ) or sulphuric acid (CNC H 2 SO 4 ) and the concentration of CNCs was 50 wt% in the electrospun mats. The surface characteristics of the nanocrystals were found to affect the dispersion, viscosity, conductivity and zetapotential of the respective spinning solutions and resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…8,9,14,15 Our earlier studies have also demonstrated that solution cast brous nanocomposite structures with high cellulose nanobers concentrations (75 wt%) and collagen provide mechanical performance suitable for ligaments. 8,9 Also, our previous studies have demonstrated the noncytotoxicity of nanocellulose from different sources and their potential in medical applications.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…8,9,14,15 Our earlier studies have also demonstrated that solution cast brous nanocomposite structures with high cellulose nanobers concentrations (75 wt%) and collagen provide mechanical performance suitable for ligaments. 8,9 Also, our previous studies have demonstrated the noncytotoxicity of nanocellulose from different sources and their potential in medical applications.…”
mentioning
confidence: 90%
“…8,9 Also, our previous studies have demonstrated the noncytotoxicity of nanocellulose from different sources and their potential in medical applications. 15,19,20 In the current study, 3D nanocomposite scaffolds for cartilage regeneration were processed via freeze-drying technique, where porous cellulose nanober structures were bound together and mechanically/dimensionally stabilized using low amounts of crosslinked chitosan/gelatin blend system. The pore structure developed during the processing is expected to impact the moisture uptake and mechanical performance of the resultant scaffolds.…”
mentioning
confidence: 99%
“…151 PVA/nanocellulose fibers also presented excellent mechanical properties. 152 PEO,153,154 PLA, 155,156 and polyvinylidenefluoride-co-hexafluoropropylene 157 have been recently tested with similar results. Other authors stressed the need for improving the compatibility between the hydrophilic nanocellulose and hydrophobic polymers.…”
Section: Other Applicationsmentioning
confidence: 98%
“…Cellulose is one of the most earth‐abundant organic materials and a major component in paper and has been recently and widely used in conjunction with electroactive and lightweight materials to fabricate flexible energy storage, plastic/coating materials, and part of the electronic devices with high flexibility and mechanical strength …”
Section: Nanocellulose Smart Materialsmentioning
confidence: 99%